Impact of slouching on heart rate variability and cardiovascular health among medical students - Nisha Ghimire; Soumitra Mukhopadhyay (Asian Journal of Medical Sciences, 2024)
Background: Medical students frequently adopt poor postures such as slouching potentially impacting health. Heart rate variability (HRV) serves as an indicator of autonomic nervous system function, correlated with cardiovascular health. Aims and Objectives: The objective of the study was to compare HRV parameters among medical students in three postures: Sitting erect, easy pose (cross-legged), and slouching (stooping head and shoulders). Materials and Methods: A comparative cross-sectional study enrolled 26 male medical students. Participants were instructed to maintain each posture for 5 min while HRV was recorded using a Polar V800. Time domain and frequency domain parameters among different postures were analyzed using Friedman’s test and post hoc tests for pairwise comparisons. P<0.05 was considered significant. Data were expressed as median interquartile range. Results: Significant differences were observed in HRV parameters between postures. The easy pose demonstrated a significantly higher median value of root mean square of differences of successive RR intervals (48.28 ms vs. 35.35 ms) and pNN50% (24.40% vs. 13.62%) compared to slouching. Frequency domain analysis revealed a significantly higher median value of high-frequency (HF) power in easy pose (626.56 ms² vs. 378.15 ms²) and HF normalized unit (33.78 vs. 22.55) compared to slouching. A lower low frequency (LF)/HF ratio and (1.96 vs. 3.43) lower LF normalized unit (66.18 vs. 77.30) was also seen in easy pose. Although statistically not significant, the parasympathetic indicators of HRV were higher in erect sitting compared to slouching posture. Conclusion: Among medical students, adopting the easy pose (cross-legged sitting) appeared to enhance HRV and thus increase parasympathetic activity, whereas adopting slouching postures decreased it.